Ezrin-Radixin-Moesin-Binding Phosphoprotein (EBP50), an Estrogen-Inducible Scaffold Protein, Contributes to Biliary Epithelial Cell Proliferation - Fouassier, Laura (American Society for Investigative Pathology, 2009)
Ezrin-radixin-moesin-binding phosphoprotein 50 (EBP50) anchors and regulates apical membrane proteins in epithelia. EBP50 is inducible by estrogen and may affect cell proliferation, although this latter function remains unclear. The goal of this study was to determine whether EBP50 was implicated in the ductular reaction that occurs in liver disease. EBP50 expression was examined in normal human liver, in human cholangiopathies (ie, cystic fibrosis, primary biliary cirrhosis, and primary sclerosing cholangitis), and in rats subjected to bile-duct ligation. The regulation of EBP50 by estrogens and its impact on proliferation were assessed in both bile duct-ligated rats and Mz-Cha-1 human biliary epithelial cells. Analyses of cell isolates and immunohistochemical studies showed that in normal human liver, EBP50 is expressed in the canalicular membranes of hepatocytes and, together with ezrin and cystic fibrosis transmembrane conductance regulator, in the apical domains of cholangiocytes. In both human cholangiopathies and bile duct-ligated rats, EBP50 was redistributed to the cytoplasmic and nuclear compartments. EBP50 underwent a transient increase in rat cholangiocytes after bile-duct ligation, whereas such expression was down-regulated in ovariectomized rats. In addition, in Mz-Cha-1 cells, EBP50 underwent up-regulation and intracellular redistribution in response to 17β-estradiol, whereas its proliferation was inhibited by siRNA-mediated EBP50 knockdown. These results indicate that both the expression and distribution of EBP50 are regulated by estrogens and contribute to the proliferative response in biliary epithelial cells.